The Influence of Access to Finance, Government Support, and Industry Collaboration on the Success of Cikarang Start-up - Meiske Wenno; Nurjanna Ladjin (Westscience Press, 2024)
This research investigates the effect of access to finance, government support, and industry collaboration on startup success in the Cikarang region through quantitative analysis. A sample of 120 startups participated in an online survey, rating their perceptions and experiences on a 5-point Likert scale. Data analysis utilized Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). Results indicate significant positive relationships between access to finance, government support, industry collaboration, and startup success. Access to finance and government support demonstrate direct positive effects on startup success, while industry collaboration acts as a mediator, enhancing the impact of financial resources on startup outcomes. The study highlights the importance of fostering a supportive regulatory environment, enhancing access to financial resources, and promoting collaborative partnerships to nurture a vibrant startup ecosystem in Cikarang.